Fungi and mycotoxins occupational exposure: unveiling the contamination in different settings from Portugal - Viegas, Carla (2023)
This study intends to present an overview of the assessments of fungal contamination and mycotoxins performed in three different occupational environments (Firefighters headquarters - FFH; Waste collection trucks – WCT and; Cemeteries - CM). Active sampling (impaction and impingement methods) and several passive sampling methods (swabs, settled dust, settled dust filters, electrostatic dust cloths – EDC, cleaning materials,…) were employed. Azole resistance screening, the molecular detection of Aspergillus sections, as well as mycotoxin analysis were also conducted. In FFH microbial contamination didn´t comply with Portuguese IAQ legal requirements in most of the FFH, the widespread of Aspergillus section Fumigati in all the FFH was observed, as well as a trend of multidrug resistance with a focus on Fumigati isolates. Several mycotoxins (fumonisin B2, nivalenol, mycophenolic acid, and sterigmatocystin) were detected. Concerning WCT Aspergillus sp. (4.18 %) was one of the most prevalent species. Aspergillus section Fumigati was detected in 5 samples. Mycotoxins were detected in filters (N=1) and in settled dust samples (N=16). The mycotoxin detected in the filter was fumonisin B1 and the most detected in settled dust was mycophenolic acid. In what concerns CM, Aspergillus sp. presented the highest counts in DG18 (18.38%) and it wasn´t observed in azole-supplemented SDA media. Mycophenolic acid was detected in one settled dust sample. Overall, our study reveals that a comprehensive sampling approach and combined analytic methods are important assets in microbial exposure assessments. Furthermore, in all three occupational environments, mycotoxins were detected unveiling this occupational health threat.